Exploration of the correlation of serum polychlorinated biphenyl levels with luteal phase hormonal parameters and infertility in women with or without polycystic ovary syndrome - Butler, Alexandra E.; Brennan, Edwina; Drage, Daniel S.; Sathyapalan, Thozhukat; Atkin, Stephen L. (Frontiers in Endocrinology, 2023)
Introduction. Polychlorinated biphenyls (PCBs) are organic lipophilic pollutants that accumulate in the body. Previous research has linked PCBs with menstrual function; therefore, this study was undertaken to investigate the correlation of PCBs with luteal phase hormonal parameters of menstrual function at day 21 in a group of non-obese women prior to in vitro fertilization (IVF). Methods. Fifty-eight non-obese Caucasian women from a UK academic center, 29 with polycystic ovary syndrome (PCOS) and 29 without, were recruited. PCOS women all had anovulatory infertility. Non-PCOS women: five with unexplained infertility, the remainder with male factor infertility (n=14) or tubal problems (n=10). Blood was withdrawn at day 21 of the menstrual cycle for non-PCOS women, at the time of mock embryo transfer. PCBs were measured using high resolution gas chromatography. Results. Only PCB118, PCB153, PCB138 and PCB180 were detected in all samples, and levels did not differ between PCOS and non-PCOS subjects. In non-PCOS subjects, PCB153, PCB138 and PCB180 inversely correlated with estradiol (p<0.05); PCB118 and PCB138 inversely correlated with follicle stimulating hormone (FSH) (p<0.05); PCB118 (p<0.05), PCB153, PCB138 and PCB180 (all p<0.01) inversely correlated with luteinizing hormone (LH). Control women without PCOS with unexplained infertility showed higher levels of PCB118, PCB153, PCB138 and PCB180 (p<0.05) compared to those control women without PCOS with tubal or male factor infertility, though other hormonal parameters did not differ other than that FSH that was lower in the unexplained group (p=0.01). The only correlation observed in PCOS women with anovulatory infertility was that between PCB180 and progesterone (p<0.05). Conclusion. PCBs correlated with luteal phase menstrual cycle hormones in control women without PCOS and may contribute to the mechanism of unexplained infertility; in PCOS women, no correlations of the PCBs were seen for estradiol, LH or FSH.